Benefits of cryopreserved human amniotic membranes in association with conventional treatments in the management of full‐thickness burns. Issue 6 (19th August 2019) - Hatzfeld, Anne‐Sophie; Pasquesoone, Louise; Germain, Nicolas; Danzé, Pierre‐Marie; Drucbert, Anne‐Sophie; Tardivel, Meryem; Bongiovanni, Antonino; Duquennoy‐Martinot, Véronique; Guerreschi, Pierre; Marchetti, Philippe
Abstract: The use of split‐thickness skin autografts (STSA) with dermal substitutes is the gold standard treatment for third‐degree burn patients. In this article, we tested whether cryopreserved amniotic membranes could be beneficial to the current treatments for full‐thickness burns. Swines were subjected to standardised full‐thickness burn injuries, and then were randomly assigned to treatments: (a) STSA alone; (b) STSA associated with the dermal substitute, Matriderm; (c) STSA plus human amniotic membrane (HAM); and (d) STSA associated with Matriderm plus HAM. Clinical and histological assessments were performed over time. We also reported the clinical use of HAM in one patient. The addition of HAM to classic treatments reduced scar contraction. In the presence of HAM, skin wound healing displayed high elasticity and histological examination showed a dense network of long elastic fibres. The presence of HAM increased dermal neovascularization, but no effect was observed on the recruitment of inflammatory cells to the wound. Moreover, the use of HAM with classical treatments in one human patient revealed a clear benefit in terms of elasticity. These results give initial evidence to consider the clinical application of HAM to avoid post‐burn contractures and therefore facilitate functional recovery after deep burn injury.